Vestibular syndrome in dairy heifers associated with Mycobacterium bovis: two case reports and strain characterization - Canton, German Jose; Marron, Yolanda; Fiorentino, María Andrea; Morrell, Eleonora Lidia; Garcia, Juan Agustin; Marfil, María; Urtizbiria, Facundo Nahuel; Morsella, Claudia Graciela; Cirone, Karina Mariela; Scioli, Maria Valeria; Zumarraga, Martin Jose; Paolicchi, Fernando (Springer, 2025)
Bovine tuberculosis is a chronic disease caused by Mycobacterium bovis which rarely causes a neurologic clinical presentation. Tuberculous meningitis is a common clinical finding in young calves in dairy herds where tuberculosis is endemic, associated with the early consumption of milk from infected cows. We report two simultaneous cases of vestibular syndrome, including loss of balance, circling, tilted head, and strabismus in 12- and 16-month-old Holstein heifers on a dairy farm in Tandil, Buenos Aires province, Argentina, with low tuberculosis prevalence (< 1.0%). Several widespread granulomatous lesions including large intracranial granulomas, characterized by a fibrous capsule containing pale yellow granular caseous material, with were observed during postmortem examination of both heifers. Microscopically, granulomas were characterized by the presence of a central caseous necrosis with mineralization, surrounded by an abundant macrophages, lymphocytes, and plasma cells infiltrate, with the presence of multiple Langhans-type giant cells, epithelioid macrophages, and connective tissue proliferation in the outer circumference. Mycobacterium bovis was isolated from different granulomas and associated lymph nodes and was typed by spoligotyping. This uncommon clinical presentation of bovine tuberculosis should be considered by veterinary practitioners, particularly in dairy herds where tuberculosis is endemic.